Role of methotrexate exposure in apoptosis and proliferation during early neurulation. Issue 8 (9th July 2013) - Wang, Xiuwei; Wang, Jianhua; Guan, Tao; Xiang, Qian; Wang, Mingsheng; Guan, Zhen; Li, Guannan; Zhu, Zhiqiang; Xie, Qiu; Zhang, Ting; Niu, Bo
ABSTRACT Apoptosis and proliferation play important roles in embryonic development and are required for neural tube closure. The antifolate drug methotrexate (MTX) induces folate dysmetabolism by inhibition of dihydrofolate reductase and causes abnormal apoptosis and proliferation. In this study, we established an animal model of neural tube defects (NTDs) using MTX to investigate the role of apoptosis and proliferation in NTDs caused by folate deficiency. Differential gene expressions were studied by microarray and reverse transcription–polymerase chain reaction in the NTD animal model. Results showed that 30.8% of NTDs were caused by using MTX in treatment regimens. Microarray indicated that 166 genes were significantly different between the control and NTD mice, including four apoptosis‐related genes (Endog, Trp53, Casp3, Bax) and three proliferation‐related genes (Ptch1, Pla2g4a, Foxg1). Levels of Endog, Trp53, Casp3, Bax (fold change > 1.5) were upregulated but Ptch1, Pla2g4a, Foxg1 (fold change < 0.67) were downregulated (P < 0.05). These results were confirmed by reverse transcription–polymerase chain reaction. TUNEL, immunohistochemical assays and Western blot were further used to detect apoptosis and proliferation in the NTD animal model. It was found that apoptosis in neuroepithelial cells was increased as determined by TUNEL (P < 0.05). Expressions of caspase‐3 were significantly enhanced (P < 0.05) but expressions of phosphohistone H3 were greatly decreased (P < 0.05). These results concluded that MTX caused a folate and folate‐associated dysmetabolism, and further induced abnormal apoptosis and proliferation, which may play a critical role in the occurrence of NTDs caused by folate deficiency. Copyright © 2013 John Wiley & Sons, Ltd.